Olive Fertility as Affected by Cross-Pollination and Boron - A. Spinardi; D. Bassi (The Scientific World Journal)
Self-compatibility of local olive (Olea europaea L.) accessions and of the cultivars “Frantoio” and “Leccino” was investigated in Garda Lake area, northern Italy. Intercompatibility was determined for “Casaliva,” “Frantoio,” and “Leccino,” as well as the effects of foliar Boron applications (0, 262, 525, or 1050 mg·L−1) applied about one week before anthesis on fruit set, shotberry set, and on in vitro pollen germination. Following self-pollination, fruit set was significantly lower and the occurrence of shot berries significantly higher than those obtained by open pollination. No significant effect of controlled cross-pollination over self-pollination on fruit set and shotberry set was detectable. B treatments increased significantly fruit set in “Frantoio” and “Casaliva” but not in “Leccino.” B sprays had no effect on shotberry set, suggesting that these parthenocarpic fruits did not strongly compete for resources allocation and did not take advantage of increased B tissue levels. Foliar B application enhanced in vitro pollen germination, and the optimal level was higher for pollen germination than for fruit set. Our results highlight the importance of olive cross pollination for obtaining satisfactory fruit set and the beneficial effect of B treatments immediately prior to anthesis, possibly by affecting positively the fertilisation process and subsequent plant source-sink relations linked to fruitlet retention.